Landslide : the final days of the Trump White House - Wolff, Michael 1953- (Henry Holt and Company, 2021)
"The story of Trump's ... last months at the helm of the country, based on [the author's] ... access to White House aides and to the former president himself, yielding a wealth of new information and insights about what really happened inside the highest office in the land, and the world"--